A Validation Study on the Pain Beliefs Questionnaire Malay Version (PBQ-M) among Malaysian Adults - Zelia HY Yong; Lee Ji Kwan; Agnes SS Chong; Zubaidah Jamil Osman (Asia Pacific Journal of Health Management)
The biopsychosocial approach in chronic pain considers one’s belief, cognition and behaviours related to the pain experience. To date, there is no measure for pain beliefs in Malaysia, highlighting the need for validation of the Pain Beliefs Questionnaire (PBQ). There were 125 participants in this cross-sectional study. The PBQ was first translated from English to Bahasa Malaysia and then back-translated by the team of researchers, reviewed and examined by third party clinical psychologists experienced in chronic pain management. While all participants completed the PBQ, only those who reported having pain exceeding six months (n = 37) were required to complete the Pain Catastrophizing Scale (PCS) and the Pain Self-Efficacy Questionnaire (PSEQ). The organic subscale had a Cronbach’s alpha coefficient of 0.81 while the psychological subscale had a coefficient of 0.71. Overall, the PBQ-M demonstrated good reliability (ICC = 0.81). The Organic subscale of the PBQ had a significant association with PCS, however, there were weak correlations between the organic (p = .058) and psychological (p = .077) subscales of PBQ with the PSEQ. In conclusion, the PBQ-M is a valid and reliable measure of Malaysian adults’ pain beliefs, independent of the presence of the condition, via two scales that can potentially predict pain catastrophizing and pain self-efficacy.